Evaluation of methods for wheat grain hardness determination - O. Faměra; M. Hrušková; D. Novotná (Plant, Soil and Environment, 2004)
Grain hardness of winter wheat cultivars was evaluated during 1997-2001 using several methods: wheat hardness index WHI (DO-Corder Brabender), 0.140 mmsieve threw ratio PPS (DO-Corder Brabender), grain hardness by NIR (Inframatic 8611 Perten), particle size index PSI (LM 3303 Perten). All tested methods showed varietal (genetic) origin of grain hardness trait and it is possible to use these methods for grain hardness determination. NIR method have had the lowest coefficient of variation (12.6%), WHI and PSI coefficient of variation was 32.8 and 30.6%, respectively. A significant influence of year-class was found only for PPS method. A high value of correlation coefficient was found between methods: WHI × NIR (r = 0.84), WHI × PPS (r = -0.79), and NIR × PPS (r = 0.74). During 2000-2001 was correlation coefficient r = -0.93 for PSI × NIR. The coefficient of variation for PSI method was 28.5%.